EXPERIENCE OF RUP “BMZ” IN THE FIELD OF CERTIFICATION OF SMK AND FINISHED PRODUCTION - V. M. Volkova; I. G. Lutsaj (Литьë и металлургия, 2007)
The backgrounds and history of creation, development of the quality system, and also practice and results of the works on certification of the quality system and production at RUP “BMZ” are considered in the article.